The Economic Effects of Road Pricing in the Randstad Area - Erik Verhoef; Mark Lijesen (Tinbergen Institute, 1998)
This paper presents a framework for analysing spatial aspects of environmentalpolicies in the regulation of trans-boundary externalities. A spatial priceequilibrium model for two regions is constructed, where interactions betweenthese regions can occur via trade and transport, via mutual environmentalspill-overs due to the externality that arises from production, and via taxcompetition when the regions do not behave cooperatively. Also the additionalcomplications arising from emissions caused by the endogenous transport flowsare considered explicitly.
Keywords: 330; Straßenbenutzungsgebühr; Randstad Holland